Synthesis of a nanomaterial from Trypan Blue and benzyldimethyldodecylamonium - Jessen, Andreas Rune Flinthom; Nielsen, Louise August; Sletfjerding, Magnus Berg; Bennekou, Patrick (UCPH NanoScience - a student research journal, 2017)
N/A